From Pupil Referral Units (PRUs) to mainstream education: a Q methodological study exploring the perceptions of PRU and mainstream secondary school professionals on reintegration - Armstrong, Hayley (2017)
Recent figures show that the number of permanent exclusions from Mainstream Secondary Schools (MSS) has increased to its highest rate in recent years (DfE, 2016c), and research suggests that reintegration back into mainstream education for young people can be problematic (Wilkin et al, 2005). Outcomes for students excluded from school and placed in alternative provision, such as Pupil Referral Units (PRUs), include social isolation, unemployment, crime, and mental health problems (Hall-Lande et al, 2007; Ofsted, 2004). However, research has suggested that effective reintegration from PRUs back into mainstream education is able to help students to reconceptualise their behaviour and break the cycle of learned helplessness (Armstrong, 1999). As research has shown that permanent exclusions often follow numerous unsuccessful transitions throughout school (Trotman et al, 2015), the importance of ensuring an effective reintegration process back into mainstream school for these students is paramount.